Patient-centered care factors and access to care: a path analysis using the Andersen behavior model. (June 2019) - Hong, YR.; Samuels, S.K.; Huo, JH.; Lee, N.; Mansoor, H.; Duncan, R.P.
Abstract: Objectives: Using the Andersen behavioral model, we examined the complex relationships among geographic access to care, financial disadvantage, patient-centered care factors, and access to care outcomes. Study design: This was a retrospective, cross-sectional study of the US civilian non-institutionalized population. Methods: Our analytic sample included 15, 787 US adults aged 18 years or older who had health insurance coverage for a full year in Medical Expenditure Panel Survey 2014–2015. Structural equation modeling was used to determine the associations among usual source of care, travel time to provider, financial disadvantage, patient-centered care factors (perceived interaction with health provider, shared decision-making, and value of health care), and access to care (perceived access to care and unmet need of health services). Results: Our analysis showed that patient-centered care factors were associated with improved perceived access to care (β = 0.03 to 0.56, P = .002) and reduced unmet needs of health care (β = −0.03 to −0.17, P = .03 to < .001). Although longer travel time to provider and having financial disadvantage of paying medical bills had negative effects on access to care outcomes, these associations were mediated by patient-centered care quality factors. Conclusions: Our findings suggest that better patient-centered care factors are associated with enhanced patient access to care. Efforts that focus on improving patient experience could be an effective approach along with coverage expansion to enhance access to quality care. Highlights: Under the Affordable Care Act, considerable disparities in access to care still exist in the US. Having health insurance may not guarantee the use of needed health services. Patient-centered care factors were associated with better patient experience with care. These associations, in turn, had positive effects on continuity of care or receipt of needed health services. Improving patient experience could be effective to enhance access to quality care.